MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SHOLAT LIMA WAKTU - Mudhoffar Mudhoffar (Jurnal Penelitian Ilmiah INTAJ, 2022)
This is classroom action research that aims to improve student learning outcomes in Jurisprudence subjects, on the material for the provisions of the five daily prayers using the “inside outside circle model”. The object of this research is the seventh-grade students of Kanigoro Performance in the 2021/2022 Academic Year. This study uses a Classroom Action Research (CAR) design which consists of two cycles. Each cycle includes four stages of activity, namely, planning, action, observation, and reflection. With descriptive technique, this classroom action research was chosen as an effort to improve student learning outcomes. Before the first and second cycles of action are taken, it begins with pre-action. At this stage the researcher made observations about the learning of fiqh that was applied in the classroom. In the implementation of this pre-action, the result was 58.09%. Then the first cycle was carried out on the Fiqh learning material on the provisions of the five daily prayers using the inside outside circle model. From the classroom action research data that the researchers got, there was a change in the first cycle. It became 75.71% but there were still 9 children whose scores had not reached the KKM. Continued to the second cycle stage to 86.66% although there are still 2 students who have not reached the KKM score. The results of the study prove that using the inside outside circle model can improve student learning outcomes in fiqh learning about the five daily prayers, in class VII MTs Al-Azhar Kanigoro Malang performance in the academic year 2021/2022.